Metastatic Breast Cancer, Organotropism and Therapeutics: A Review - Waza, Ajaz A.; Tarfeen, Najeebul; Majid, Sabhiya; Hassan, Yasmeena; Mir, Rashid; Rather, Mohd Younis; Shah, Naseer U. D. (Current Cancer Drug Targets, 2021)
The final stage of breast cancer involves spreading breast cancer cells to the vital organs like the brain, liver lungs and bones in the process called metastasis. Once the target organ is overtaken by the metastatic breast cancer cells, its usual function is compromised causing organ dysfunction and death. Despite the significant research on breast cancer metastasis, it’s still the main culprit of breast cancer-related deaths. Exploring the complex molecular pathways associated with the initiation and progression of breast cancer metastasis could lead to the discovery of more effective ways of treating the devastating phenomenon. The present review article highlights the recent advances to understand the complexity associated with breast cancer metastases, organotropism and therapeutic advances.
Keywords: organotropism